Leading a grassroots movement in a large organization - Svobodová, Markéta, (SAGE Business cases., 2024)
In this case study, students explore an example of a female leader from a position below lower management who led a grassroots movement at a large company (with more than 1,000 employees) producing household appliances and operating in Western and Central Europe. In this scenario, sustainability and resistance-blocking limitations were worked through. This case shows how, under certain conditions, resistance leadership in sustainability can emerge even in a complex, bureaucratic, hierarchical manufacturing organization with many obstacles along the way. The key success factors of leading this grassroots movement are revealed. When such a bottom-up change is managed, it brings benefits to the company, its employees, and society. The goal of this case is to show how a change toward improving sustainability can happen in practice and increase students' understanding about change management, possible obstacles (including path dependency), and key success factors. Dilemmas faced by the female leader included whom to involve in the discussions and whom to try to persuade about the importance of the topic to get the official approval.